Proceedings of the 11th Toulon-Verona International Conference on Quality in Services Higher Education, Health Care, Local Government, Tourism, Banking - Martin, Jacques; MOLITERNI, ROCCO (Proceedings e report, 2008)
The Toulon-Verona Conference was founded in 1998 by prof. Claudio Baccarani of the University of Verona, Italy, and prof. Michel Weill of the University of Toulon, France. It has been organized each year in a different place in Europe in cooperation with a host university (Toulon 1998, Verona 1999, Derby 2000, Mons 2001, Lisbon 2002, Oviedo 2003, Toulon 2004, Palermo 2005, Paisley 2006, Thessaloniki 2007, Florence, 2008). Originally focusing on higher education institutions, the research themes have over the years been extended to the health sector, local government, tourism, logistics, banking services. Around a hundred delegates from about twenty different countries participate each year and nearly one thousand research papers have been published over the last ten years, making of the conference one of the major events in the field of quality in services.